2011
DOI: 10.1007/s10509-011-0759-x
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational collapse in generalized Vaidya space-time for Lovelock gravity theory

Abstract: In this work, we have assumed the generalized Vaidya solution in Lovelock theory of gravity in (n + 2)-dimensions. It has been shown that Gauss-Bonnet gravity, dimensionally continued Lovelock gravity and pure Lovelock gravity can be constructed by suitable choice of parameters. We have investigated the occurrence of singularities formed by the gravitational collapse in above three particular forms of Lovelock theory of gravity. The dependence of the nature of singularity on the existence of radial null geodes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 45 publications
1
32
3
Order By: Relevance
“…Gravitational collapse has been extensively studied in modified gravity theory i.e., in Gauss-Bonnet, f (R) gravity, Lovelock theory etc [28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. Scheel [47] demonstrated that Openheimer-Snyder collapse in Brans-Dicke theory results in BHs rather than NSs with the positive values of brans-dicke parameter ω, they have speculated that the apparent horizon of a BH can pass outside the event horizon causing the decrease in the surface area over time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gravitational collapse has been extensively studied in modified gravity theory i.e., in Gauss-Bonnet, f (R) gravity, Lovelock theory etc [28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. Scheel [47] demonstrated that Openheimer-Snyder collapse in Brans-Dicke theory results in BHs rather than NSs with the positive values of brans-dicke parameter ω, they have speculated that the apparent horizon of a BH can pass outside the event horizon causing the decrease in the surface area over time.…”
Section: Introductionmentioning
confidence: 99%
“…The values of ω forces the BH, to radiate its scalar mass to infinity soon after the initial collapse. In [48] we get another relevant and interesting work regarding the gravitational collapse in the background of Brans-Dicke theory of gravity discussing the effects of different values of ω. Rudra et al in [49] has shown that lower the value of ω, greater is the chance of getting an NS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have seen that higher dimensional background increases the possibilities to have a naked singularity rather than a BH spacetime wrapped by an event horizon [67,68]. That is, the BHs are less stable in higher dimensions.…”
Section: Discussionmentioning
confidence: 89%
“…Detailed study of continual gravitational collapse of these spacetimes in the context of the Cosmic Censorship Conjecture were done in [22,23]. In the geometrical context, gravitational collapse has been considered in Lovelock gravity theory [24], black holes in dynamical cosmology backgrounds [25] and in electromagnetic fluids [26]. The influence of dust, radiation, quintessence and the cosmological constant are included in these studies.…”
Section: Introductionmentioning
confidence: 99%